Improving preschool nutrition: addressing knowledge and practice gaps among nursery staff in Amman, Jordan - Al-Mahshi, Hadieh; Haddad, Areen; Musharbash, Ruba; Jahrami, Haitham; Amawi, Adam; Ghazzawi, Hadeel (Frontiers in Nutrition, 2025)
BackgroundPreschoolers attending nurseries typically spend a significant period of their day in nurseries, where they consume approximately half or more of their daily meals under the supervision of nursery staff. As the primary caregivers during this time, nursery staff play a vital role in forming children’s eating habits and influencing their nutritional intake. Thus, assessing the nutritional knowledge and practices of nursery staff is essential.ObjectiveTo assess the nutritional knowledge and practices of nursery staff members.MethodsA cross-sectional study was conducted among nursery staff. A self-administered questionnaire was used to assess the nutritional knowledge and practices of the nursery staff members.ResultsA total of 53.2% of the nursery staff exhibited high levels of nutritional knowledge, whereas 3.2% showed low nutritional understanding. Additionally, approximately 50% of the nursery staff displayed excellent dietary behaviors, while 6.4% showed inadequate standards.ConclusionNursery staff possess preliminary nutrition knowledge but need guidance and training sessions in nutrition that may enhance their essential role in improving preschoolers’ nutritional status and health.